Effects of several flavonoids on human gut microbiota and its metabolism by in vitro simulated fermentation - Pan, Lixia; Ye, Hangyu; Pi, Xionge; Liu, Wei; Wang, Zhao; Zhang, Yinjun; Zheng, Jianyong (Frontiers in Microbiology, 2023)
Flavonoids have antiviral, antitumor, anti-inflammatory, and other biological activities. They have high market value and are widely used in food and medicine fields. They also can regulate gut microbiota and promote human health. However, only a few flavonoids have been reported for their regulatory effects on human gut microbiota. The effects of hesperidin, hesperetin-7-O-glucoside, hesperetin, naringin, prunin, naringenin, rutin, isoquercitrin, and quercetin on gut microbiota structural and metabolic differences in healthy subjects were studied by means of in vitro simulated fermentation technology. Results showed that the nine kinds of flavonoids mentioned above, especially hesperetin-7-O-glucoside, prunin, and isoquercitrin, were found to have more effect on the structure of human gut microbiota, and they could significantly enhance Bifidobacterium (p < 0.05). After 24 h of in vitro simulated fermentation, the relative abundance of intestinal probiotics (e.g., Lactobacillus) was increased by the three flavonoids and rutin. Furthermore, the the relative abundance of potential pathogenic bacteria was decreased by the addition of hesperetin-7-O-glucoside, naringin, prunin, rutin, and isoquercitrin (e.g., Lachnoclostridium and Bilophila). Notably, prunin could also markedly decrease the content of H2S, NH3, and short-chain fatty acids. This performance fully demonstrated its broad-spectrum antibacterial activity. This study demonstrates that flavonoids can regulate the imbalance of gut microbiota, and some differences in the regulatory effect are observed due to different structures. This work provides a theoretical basis for the wide application of flavonoids for food and medicine.